P543 Induction and maintenance of mucosal healing in Crohn's disease with ustekinumab in clinical practice – Results of a nationwide, prospective, multicenter study in Germany (MUCUS). (30th January 2023) - Baumgart MD PhD MBA, D C; Stallmach, A; Schubert, A; Howaldt, S; von Arnim, U; Ochsenkühn, T; Stein, J; Lügering, A; Schmidt, D; Schulz, M; Fischer, A
Abstract: Background: Ustekinumab (UST) is a fully human IgG1k monoclonal antibody to human IL-12/23p40 approved in several jurisdictions for the treatment of adult patients with moderately to severely active Crohn's disease (CD). UST's impact on induction and maintenance of mucosal healing, fistula healing and extraintestinal manifestations were not fully elucidated in the registration trial program. Methods: In this prospective, multicenter study (EudraCT number: 2017-005151-83) across all care levels in Germany, we evaluated the real-world effectiveness of UST prescribed within its German label to achieve the primary endpoint of combined clinical (Harvey Bradshaw Index (HBI) score reduction ≥ 3 points from baseline) and endoscopic (50% reduction of the simple Endoscopic Score for Crohn Disease (SES-CD) from baseline) response in week 52 and a variety of secondary endpoints including mucosal healing defined as the complete absence of mucosal ulcerations in any ileocolonic segment and endoscopic remission defined as an SES-CD score of 0 – 2. Results: We recruited 52 CD patients (female n=28, bionaive n=13, bioexposed n=39). See Table 1 for baseline demographics and pertinent history details. At week 52, 50% (n=12/24) of patients achieved the primary endpoint [50% (n=3/6) in the bionaive, 45.5% (n=5/11) bioexposed to one and 57.1% (n=4/7) bioexposed to multiple biologics cohorts, respectively], 58.3% (n=14/24) of patients achieved endoscopic response [50% (n=3/6) in the bionaive, 54.5% (n=6/11) bioexposed to one and 71.4% (n=5/7) bioexposed to multiple biologics cohorts, respectively], 33.3% (n=8/24) of patients achieved endoscopic remission [50% (n=3/6) in the bionaive, 27.3% (n=3/11) bioexposed to one and 28.6% (n=2/7) bioexposed to multiple biologics cohorts, respectively], 45.8% (n=11/24) of patients achieved mucosal healing [50% (n=3/6) in the bionaive, 36.4% (n=4/11) bioexposed to one and 57.1% (n=4/7) bioexposed to multiple biologics cohorts, respectively]. 36 patients (69.2%) experienced ≥ 1 treatment emergent adverse event (TEAE), in 8 (15.4%) cases rated as severe and in 5 (9.6%) leading to discontinuation of UST, but no very severe events or deaths (Table 2). Conclusion: UST reliably induces endoscopic response and mucosal healing in both bionaive and bioexperienced CD patients in routine clinical practice. The limited samples size is a direct result from the Covid-19 pandemic. No new safety signals were recorded.